Uji Efek Antiinflamasi Ekstrak Etanol Rimpang Jahe (Zingiber officinale Roscoe) pada Tikus Putih Jantan - Surya Dharma; Eka Santi Adelinda; Netty Suharti (Jurnal Farmasi Higea, 2009)
Effect of antiinflamantory extract ginger rhizome ethanol has been observed on white male mice. Extract is given buccally with dose 30, 100, 300 mg/kg BB, while preparation is becoming with dose 360 mg/kg BB. Parameter antiinflamantory observed with calculating ability of extract and preparation thus ginger lessens or depress degree of oedema during certain. Level of oedema volume happened is measured by means of pletisnometer. The result of research indicates that ginger ethanol extract at dose 30, 100, 300 mg/kg BB and preparation thus ginger with dose 360 mg/kg BB gives effect antiinflamantory. Highest effect given by ginger extract with dose 300 mg/kg BB with inhibition percentage happened at to 6 at day ke-10 that is 84%. And result of statistician examination in analysis variansi ( ANOVA) to oedema volume after giving of ethanol extract and preparation became ginger to give effect antiinflamantory which real is different if it is compared to control.